2019
DOI: 10.1007/s00167-019-05523-1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging can increase the diagnostic accuracy in symptomatic meniscal repair patients

Abstract: Purpose The purpose of this study was to evaluate meniscal repair healing in symptomatic patients through combined clinical assessment, magnetic resonance imaging (MRI) and re-arthroscopy. This study investigated the diagnostic accuracy of MRI and clinical assessment in determining failed meniscal repair in symptomatic meniscal repair patients, as verified by re-arthroscopy. Methods Eighty patients were included. All had undergone a primary meniscal repair followed by an MRI and re-arthroscopy due to clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Similarly, PDW MRIs may have detected the healing process of the repaired LM in patients who underwent anatomic ACLR. Because previous MRI reports included patients who underwent isolated meniscus repair, 10 , 31 , 43 these studies imply that T2W sequences would be preferable for detecting insufficient healing of the isolated meniscal repair. However, the current study was related to the concomitant lateral meniscal tear with ACL tear: the diagnostic performance to detect incomplete healing of focal LM posterior horn tear concomitant with an ACL tear may be superior on PDW compared with T2W sequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, PDW MRIs may have detected the healing process of the repaired LM in patients who underwent anatomic ACLR. Because previous MRI reports included patients who underwent isolated meniscus repair, 10 , 31 , 43 these studies imply that T2W sequences would be preferable for detecting insufficient healing of the isolated meniscal repair. However, the current study was related to the concomitant lateral meniscal tear with ACL tear: the diagnostic performance to detect incomplete healing of focal LM posterior horn tear concomitant with an ACL tear may be superior on PDW compared with T2W sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data indicated that the increased signal density of repaired LM on MRI scans corresponded to the incomplete healing of meniscal tissue confirmed by second-look arthroscopy. 10 , 31 , 43 , 49 Based on current data, the increased SI of repaired LM has the potential to explain why the repaired meniscal tissue failed to heal and restore its function to stabilize the ALLx after lateral meniscal repair. At the same time, the current data could not exclude the possibility of the other direction: the residual ALLx provokes the nonhealing or delayed healing of the repaired LM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of clinical outcomes to assess whether a meniscus is healed is known to be poor [11, 19]. The presence of tibiofemoral joint symptoms does not always distinguish between healed and unhealed meniscal lesions, and is not directly related to biological healing of the meniscus [17].…”
Section: Discussionmentioning
confidence: 99%
“…To assess healing, most studies look at clinical outcomes after meniscal repair, such as Patient Reported Outcome Measures (PROMs) or clinical tests, or imaging modalities such as MR imaging. The sensitivity, specificity and accuracy of clinical outcomes and different imaging modalities to determine biologically complete healing remains limited [11, 16, 17, 19, 27]. The most reliable technique to evaluate complete meniscal healing is second‐look arthroscopy [17].…”
Section: Introductionmentioning
confidence: 99%